Students’ preference and purchasing decision through mobile network advertisements (2015)
Studies in advertising show that although television advertisements and product placements introduce viewers to products or act as a reminder, many times consumers make their purchase through another medium. Employing media dependency theory, the study adopted the survey research method using quantitative and qualitative data gathering methods. 400 students of Polytechnic Ibadan were sampled for the survey questionnaire while focus group discussions were held with other students of the institution. Quantitative data were analysed using frequency count and T-test while qualitative data were coded with relevant issues selected to support the findings. There is a significant correlation between mobile television advertisements and consumer purchasing decision (Pearson=.622, p<002). This means that the more mobile network advertisements people watch, the more likely there is an influence in their choice of mobile network products and services at the point of purchase. The use of music, slogans and drama serves as aesthetics in influencing respondents through advertisement messages; hence they see the advertisements as captivating, true, informative, educative, entertaining and convincing. This implies that television advertisement is productive in influencing consumers' decision, hence mobile network service providers need to be more creative and strategic in placing advertisements on television due to high competition within the industry.